Formaldehyde production via hydrogenation of carbon monoxide in the aqueous phase. Issue 6 (8th June 2015) - Bahmanpour, Ali Mohammad; Hoadley, Andrew; Tanksale, Akshat
<x xml:space="preserve">Abstract</x> Discovery of a low temperature route to produce formaldehyde via catalytic hydrogenation of carbon monoxide in the aqueous phase.